Improving the quality of social service in hospitals and health centers according to the vision of the Kingdom 2030 - Al Qahtani, Rafa'an Hamad (Journal of Humanities & Social Sciences, 2018)
The study aimed at identifying the reality of social service in Saudi hospitals and health centers, and the standards of evaluating its quality, moreover the mechanisms of development according to the kingdom vision 2030; this is a descriptive analytical study; the study results revealed that the social medical service in the hospitals and medical centers in the Kingdom of Saudi Arabia is being greatly interested in the officers; the study results revealed that the development of the quality of social service introduced in the hospital and health center matches the Kingdom vision 2030 which is clearly interested in developing the health sector to improve the quality of health services including both preventive and treatment parts.
Keywords: quality; social service; hospitals; health centers; Saudi Vision 2030